KUFRI LALIT: A LIGHT RED SKIN POTATO VERIETY FOR EASTERN PLAINS - Kumar, Shambu; Eradasappa, E; Kumar, Vinod (Potato Journal, 2018)
KUFRI LALIT: A LIGHT RED SKINNED POTATO VARIETY FOR EASTERN PLAINS Shambhu Kumar1 , E Eradasappa1 , Vinod Kumar2 and B Prasad1 ABSTRACT: Kufri Lalit (2001- P-55) is a selection from the cross 85-P-670 âˆš CP3192 and is a medium maturing variety (80- 90 days duration). Its tubers are attractive having light red skin, round shaped, yellow flesh and firm tubers with medium deep eyes having moderate dry matter content (18%). It also possesses good keeping quality, medium tuber dormancy period (>6 weeks) and field resistance to late blight comparable with Kufri Himalini. It also produced higher average tuber yield (15.81%) than Kufri Lalima in trials conducted across the eastern plains of India. In a three year trial at Patna it produced 24% higher yield than Kufri Arun. The variety can aptly replace the existing red skinned varieties Kufri Lalima, Kufri Sindhuri and Kufri Arun on account of higher yield, better resistance to late blight and better keeping quality